BOOK REVIEW: FLORIN ONCESCU, “JURNALUL LUI SAKE [SAKE’S DIARY]”. CLUJ-NAPOCA: LIMES, 2017, 224 P. - KOSA, Monika (Studia Universitatis Babeș-Bolyai Philologia, 2019)
Florin Oncescu’s most recently published novel, Jurnalul lui Sake [Sake’s Diary], is a delightful and humorous piece of writing that playfully thematizes contemporary issues such as the complex articulations of relocation and bicultural identities. Florin Oncescu is a prominent and idiosyncratic contemporary Romanian writer, who was born in 1960 in Constanța. He has graduated from Polytechnic University of Bucharest in 1985 and permanently moved to Canada in 1995. He has been living in Montréal ever since, with short periods spent in the United States. Nevertheless, he is a well-known and active writer in the Romanian literary landscape. Florin Oncescu has published several volumes of fiction so far: Dispoziție depresivă (Ramuri, Craiova, 1994), La umbra unui enciclopedist (Omniscop, Craiova, 1999), Întoarcerea (Ramuri, Craiova, 2003), Ilustrate din America (Limes, Cluj-Napoca, 2007). He is a member of the Romanian Writers’ Union and regularly publishes in Pagini românești.